Heuristic strategies in solving mathematical problems in a primary school in Peru - Vargas-Fernández, Mercedes (2025)
The study addressed the difficulties faced by fourth-cycle primary school students in public educational institutions in the district of Ccatca, Cusco region, in solving mathematical problems. These difficulties were attributed to the limited use of effective strategies and heuristic techniques by teachers. The main objective is to analyze the impact of applying these strategies on student performance and to propose a pedagogical model based on empirical evidence. A heuristic strategy was applied in an applied study with a pre-experimental design, involving 131 students. To measure progress, a pedagogical test (pretest and posttest) and an evaluation rubric were used. The data were analyzed using SPSS 22 and Excel. In the pretest, 67.2% of students were at the "beginning" level, 21.4% were "in process," and only 11.5% reached the "expected achievement" level. After the intervention, these results reversed: 0% at "beginning," 33.6% "in process," and 66.4% at "expected achievement." Significant improvements were observed in all evaluated dimensions, particularly in reading and comprehension (67.2%) and planning and translation (62.6%). It is concluded that the application of heuristic strategies strengthens students’ cognitive and methodological abilities, promoting more autonomous, reflective, and effective learning. The results support the integration of these strategies into mathematics instruction, especially in low-performing educational contexts.